IMPLEMENTASI KEBIJAKAN BANTUAN OPERASIONAL SEKOLAH ( BOS ) DI SDN TLOGOSARI WETAN 01 KECAMATAN PEDURUNGAN KOTA SEMARANG - Galih Wardana; Slamet Santoso; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Education is a planned effort in the development of self in order to realize the potential of a civilized society, morality, personality, intelligent and have a prosperous life skills (spiritual-knowledged based society). Which is currently able to improve the quality of education in Indonesia is through fund School Operational Assistance (BOS) allocated to schools at primary and secondary School Operational Assistance Program is a central government assistance to all students SD / MI and SMP / MTs underprivileged throughout Indonesia both public and private on reduction of fuel subsidy because it was feared that the increase in fuel prices and the global financial crisis caused a decline in purchasing power and will negatively impact the poor to get an education.The purpose of the research to find out and get a clear picture about the implementation of the BOS program on SDN Tlogosari Wetan 01 Sub Pedurungan, and used materials and used as an ingredient on the study of the implementation of the BOS program on SDN Tlogosari Wetan 01 Sub Pedurungan, Semarang.In this research used theory implementation of G Edward III which states